Pengaruh Penambahan Superplasticizer SR 300 Terhadap Kuat Tekan Beton fc’ 26,4 MPa - Asrullah, Asrullah; Anggrainy, Rita; Ismail, Ayu; Suciati, Indah (Jurnal Teknik Sipil, 2024)
The world of construction is currently experiencing very rapid development. This can be seen from various countries that are competing to improve the quality and quantity of their buildings. Indonesia is one of the developing countries that is increasing infrastructure development with the aim of supporting services to the community. The purpose of this study was to determine the effect of the addition of Superplasticizer SR 300. The purpose of this study is to determine the effect of the addition of Superplasticizer SR 300 on the compressive strength of concrete fc' 26.4 MPa, the method used in the compressive strength test is SNI 03-2834-2000. The results of this study can be concluded as follows; Standard concrete compressive strength (BS) of 26.59 Mpa, the largest concrete compressive strength value with the addition of SR 300 by 1.5% (SR300-1) aged 28 days of 28.02 MPa, a simple regression model with the equation Y = -1.822x + 29.275, and the coefficient of determination R2 bernilain 0.6919, the addition of SR 300 influences the value of concrete compressive strength and specific gravity of concrete aged 28 days categorized as normal concrete.